Informal health sector and routine immunization: making the case for harnessing the potentials of patent medicine vendors for the big catch-up to reduce zero-dose children in sub-Saharan Africa - Adamu, Abdu A.; Jalo, Rabiu I.; Ndwandwe, Duduzile; Wiysonge, Charles S. (Frontiers in Public Health, 2024)
The COVID-19 pandemic caused a surge in the number of unimmunized and under-immunized children in Africa. The majority of unimmunized (or zero-dose) children live in hard-to-reach rural areas, urban slums, and communities affected by conflict where health facilities are usually unavailable or difficult to access. In these settings, people mostly rely on the informal health sector for essential health services. Therefore, to reduce zero-dose children, it is critical to expand immunization services beyond health facilities to the informal health sector to meet the immunization needs of children in underserved places. In this perspective article, we propose a framework for the expansion of immunization services through the informal health sector as one of the pillars for the big catch-up plan to improve coverage and equity. In African countries like Nigeria, Ethiopia, Tanzania, and the Democratic Republic of Congo, patent medicine vendors serve as an important informal health sector provider group, and thus, they can be engaged to provide immunization services. A hub-and-spoke model can be used to integrate patent medicine vendors into the immunization system. A hub-and-spoke model is a framework for organization design where services that are provided by a central facility (hub) are complimented by secondary sites (spokes) to optimize access to care. Systems thinking approach should guide the design, implementation, and evaluation of this model.